2021
DOI: 10.28991/cej-2021-03091719
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Traffic Accidents Density on Selected Multilane Rural Highways

Abstract: Estimations of average crash density as a function of traffic elements and characteristics can be used for making good decisions relating to planning, designing, operating, and maintaining roadway networks. This study describes the relationships between total, collision, turnover, and runover accident densities with factors such as hourly traffic flow and average spot speed on multilane rural highways in Iraq. The study is based on data collected from two sources: police stations and traffic surveys. Three hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…When examining traffic flow on a specific section of the road, several overarching factors come into play. These include the overall road infrastructure both within and outside the section being studied [88][89][90], as well as temporary factors that can be cyclic, like changes in time of day and seasons [35,91,92], or random, such as variations in weather conditions [93].…”
Section: Analysis Of the Influence Of The Dynamics Of The Pts On The ...mentioning
confidence: 99%
See 1 more Smart Citation
“…When examining traffic flow on a specific section of the road, several overarching factors come into play. These include the overall road infrastructure both within and outside the section being studied [88][89][90], as well as temporary factors that can be cyclic, like changes in time of day and seasons [35,91,92], or random, such as variations in weather conditions [93].…”
Section: Analysis Of the Influence Of The Dynamics Of The Pts On The ...mentioning
confidence: 99%
“…These global and temporal factors also fluctuate and influence traffic flow characteristics to different extents, which can make simulation modeling quite complex [35,92]. To simplify this complexity, a limited set of traffic flow parameters is required to develop SMTF and assess the dynamics of each parameter.…”
Section: Analysis Of the Influence Of The Dynamics Of The Pts On The ...mentioning
confidence: 99%
“…When examining traffic flow on a specific section of the road, several overarching factors come into play. These include the overall road infrastructure both within and outside the section being studied [60][61][62], as well as temporary factors that can be cyclic, like changes in time of day and seasons [23,63,64], or random, such as variations in weather conditions [65].…”
Section: Analysis Of the Influence Of The Dynamics Of The Pts On The ...mentioning
confidence: 99%
“…These global and temporal factors also fluctuate and influence traffic flow characteristics to different extents, which can make simulation modeling quite complex [23,64]. To simplify this complexity, a limited set of traffic flow parameters is required to develop SMTF and assess the dynamics of each parameter.…”
Section: Analysis Of the Influence Of The Dynamics Of The Pts On The ...mentioning
confidence: 99%
“…In addition, several researches have been conducted to study the road safety issue in Iraq and consider the various factors. Al-Dulemi [10] found that the lane marking has significant effect on the road safety level of rural road in Iraq while Jrew et al [11] found that road length, lane width, number of lanes, traffic density, and number of speed calming, number of pedestrian bridges and crosswalks, and the availability of median have higher impact in road network in Erbil city. Aldoski et al [12] focused more in his research on surface and addressed its significant effect on the road risk level while Diah et al [13] and Albayati and Lateif [14] highlighted the impact of road functional classification and the lighting in increasing the road accidents.…”
Section: Introductionmentioning
confidence: 99%